Analysis of the interactions between small pulmonary nodules, clinical factors and the risk of malignancy in the chest following diagnosis of head and neck cancer. (2nd March 2022) - Macmillan, Mark T.; Hopkins, Michael E.; Gomati, Anas; Subedi, Deepak; Reid, Helen; Bruce, Lorna; Murchison, John T.; Nixon, Iain J.
Abstract: Background: This study aims to investigate radiological and clinical factors which predict malignancy in indeterminate pulmonary nodules in patients with head and neck cancer (HNC). Methods: Prospective data were collected in 424 patients who were reviewed in the NHS Lothian HNC multidisciplinary meeting from May 2016 to May 2018. Staging and follow‐up CT chest imaging were reviewed to identify and assess pulmonary nodules in all patients. Results: About 61.8% of patients had at least one pulmonary nodule at staging CT. In total, 25 patients developed malignancy in the chest. Metastatic disease in the chest was significantly associated with unknown or negative p16 status ( p < .0005). Pleural indentation and spiculation were associated with indeterminate nodules, subsequently being shown to represent metastatic disease ( p > .0005 and p = .046, respectively). Conclusion: Negative or unknown p16 status was associated with an increased propensity to develop metastatic disease in the chest in patients with HNC.